FAKTOR PENGHAMBAT PEMERINTAH DAERAH KABUPATEN SIAK DALAM MENGELOLA KAWASAN WISATA HUTAN ZAMRUD TAHUN 2013 – 2015 - Kartini "; Auradian Marta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The potential of the Siak diversity of potential tourist objects makes Siak has promising prospects for tourism development. In a sense, the tourism product is a potential vary widely in marketing and determining the travel market segmentation so that tourists visiting the Siak could increase. Management and development based on local regulation number 12 of 2012 on Regional Tourism Development Master Plan, especially at points Siak Nature emerald forest tourist area has great potential to be made tourist attractions.This research uses descriptive analysis method using a qualitative approach, which is located in Siak district with a focus on the factors - factors that constrain District Government Siak manage tourist area of forest emerald by the Department of Tourism, Youth and Sports towards tourism forest of 38,000 potentially huge as tourist attraction.Based on this research can be concluded Siak district government through the Department of Tourism, Youth and Sports in implementing tungas and functions to develop and manage natural attractions emerald forest area is not maximized. It can be seen from four variables inhibiting factor, namely the budget, infrastructure, partnerships and human resources.Keyword : Inhibiting Factors, Nature, Zamrud Forest